2019
DOI: 10.1007/s11145-019-09934-x
|View full text |Cite
|
Sign up to set email alerts
|

Improving Hindi decoding skills via a mobile game

Abstract: Previous research with alphasyllabaries has shown that children struggle with akshara that have two or more consonants, known as complex akshara. We developed a mobile game that teaches 4th grade children Hindi decoding skills, with an emphasis on complex akshara. All of the children were second language learners of Hindi.There were two versions of the game that varied in terms of stimuli spacing (massed and distributed). We found that the game improved participants' akshara recognition and their ability to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…The significance levels were higher for the intermediate and advanced levels, potentially indicating that the game can facilitate the teaching of advanced Arabic orthography skills. These findings align with those of other studies; that is, significant improvements in learner performance are achieved when integrating mobile games into teaching and learning environments ( (Prensky, 2001;Chaves et al, 2018;Bhide et al, 2019;Acquah et al, 2019;Sandberg et al, 2011;Ahmad, Arab World English Journal www.awej.org ISSN: 2229-9327 158 Shaarani & Afrizal, 2012Cho, Lee, Joo, & Becker, 2018). In all of these studies, researchers concluded that the integration of mobile games enhanced learning outcomes and had significant impacts on students' scores.…”
Section: Students' Performancesupporting
confidence: 86%
See 2 more Smart Citations
“…The significance levels were higher for the intermediate and advanced levels, potentially indicating that the game can facilitate the teaching of advanced Arabic orthography skills. These findings align with those of other studies; that is, significant improvements in learner performance are achieved when integrating mobile games into teaching and learning environments ( (Prensky, 2001;Chaves et al, 2018;Bhide et al, 2019;Acquah et al, 2019;Sandberg et al, 2011;Ahmad, Arab World English Journal www.awej.org ISSN: 2229-9327 158 Shaarani & Afrizal, 2012Cho, Lee, Joo, & Becker, 2018). In all of these studies, researchers concluded that the integration of mobile games enhanced learning outcomes and had significant impacts on students' scores.…”
Section: Students' Performancesupporting
confidence: 86%
“…Mobile learning games have been shown to have significant impacts on language learning. Mobile learning games have gained considerable popularity among young learners in recent years, and many researchers believe that such games can enhance the teaching-learning environment (Yamato, Corrêa, & Martins2017;Chaves et al, 2018;Bhide et al, 2019;Vanbecelaere et al, 2019;Juhani Lyytinen, Semrud-Clikeman, Pugh & Richardson, 2021;Alotaibi, & Alharbi,2022;Amorim et al, 2022). According to Johnson et al, (2013), mobile learning games significantly promote engagement, creativity, and authentic learning.…”
Section: Literature Review Mobile Learning Gamesmentioning
confidence: 99%
See 1 more Smart Citation
“…It will not be possible to ascertain the learning potential of such new technologies without carefully controlled, theoretically driven studies. There was also a lack of included studies focussed on games, despite the popularity of games as a tool for teaching language (Bhide et al, 2019;Duh, Koceska, & Koceski, 2017;Samur, 2019). Thus, there are many gaps in the extant literature which are open to be addressed in future research.…”
Section: Limitations Of Existing Literaturementioning
confidence: 99%